AI and communication research: Reassessing theory and methodology in the age of automation - Prahastiwi Utari; Pramana Pramana; Eka Nada Shofa Alkhajar (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
The rapid development of artificial intelligence (AI) marks a fundamental shift in communication science, positioning AI not only as a research tool but also as an active entity in the communication process. This paper argues for a paradigm shift from conventional human to human interaction toward beyond human communication, where AI functions as communicator, medium, and message producer. Such transformation requires re-examining communication theories in interpersonal, mass, and technological contexts within a convergent framework. At the theoretical level, communication must be repositioned to address new ontological and epistemological questions. Methodologically, AI offers opportunities through big data and automated analysis while raising ethical challenges such as algorithmic bias and the risk of reducing communication to technical processes. This paper proposes a reflective critical approach that emphasizes adaptive, convergent, and contextual communication theories, ensuring the discipline remains relevant in the era of artificial intelligence.